PEMANFAATAN ROTAN DAN BAMBU OLEH MASYARAKAT DESA PARIT RAJA KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Suryani, Cici; Zainal, Sofyan; Nurhaida, Nurhaida (JURNAL HUTAN LESTARI, 2019)
Forests have the potential to meet a variety of human needs such as food, medicine, timber, and handicraft. Non-timber forest product used by the community of Parit Raja Village are rattan and bamboo. This research aim to inventory of the types of rattan and bamboo and to inventory the forms of utilization of rattan and bamboo processing in Parit Raja Village ofÂ  Sejangkung Sub-District of Sambas Regency. This study used a survey method with in-depth interviews with the community in Parit Raja Village. The results showed that there were 5 types of rattan and 3 types of bamboo that were utilized by people of Parit Raja Village, namely Seuti Rattan (Calamus ornatus), Marau Rattan (Korthalsia rigida), Sega Rattan (Calamus caesius), Babuai Rattan (Plectocomia elongate), Nanga Rattan (Korthalsia Junghuhnii) and Bambo, namely Abe Bamboo (Gigantochloa Balui), Kuayan Bamboo, Ater Bamboo (Gigantochloa atter). The forms of utilization of rattan by Parit Raja Village community are the furniture, living room decoration and wicker found in the Sejangkung Hamlet. The most common type of rattan used were Seuti (99.9%), while bamboo utilization ranged from furniture, wicker and cooking as found in Gambir Hamlet, Kawakan Hamlet, Sembuai Hamlet, and Rambayan Hamlet. The most commonly used bamboo species is Abe bamboo (93,3%). There are 22 handicraft product produced by the people of Parit Raja Village including sofa sets, baby swing baskets, room dividers, corner shelves, flower vases (cage model), and parcels. The forms of utilization of bamboo by the community of Parit Raja Village: there are 14 handicraft products including nyiru, capil/tanggoi, rice dishes, small rice basket, bakak ( large rice basket), and fruit basket.Â Keywords: Rattan, Bamboo, Parit Raja Village, Handicrafts.